The candle in the window - Johnson, Grace, 1932-; Elliott, Mark, 1967- (Grand Rapids, Mich. : Fleming H. Revell, 2003)
Gunther, a cobbler, is a lonely man who has lost all joy and hope until a visit from three strangers who place a candle in his window changes everything, and suddenly Gunther is caught up in the excitement of waiting for the Christ Child's visit.
"Based on a story by Leo Tolstoy"--Jacket.
Keywords: Christmas stories; Germany -- Juvenile fiction; Christmas -- Fiction; Conduct of life -- Fiction; Germany -- Fiction; Christmas stories; Germany; Fiction; Juvenile works